Acoustical Impact of Ships and Harbours: Airborne and Underwater N&V Pollution - Davide Borelli (Frontiers Research Topics, 2019)
Noise and vibrations generated by ships affect a wide range of receivers: crew and passengers inside the vessel, inhabitants of the coastal areas and marine fauna outside it. Recent studies suggest that a large percentage of people living in urban areas close to harbors and a number of marine species, at different evolutionary levels (in particular mammals and cephalopods), suffer from ship N&V emissions in air and in water. The present degree of knowledge of the phenomena involved in the noise emissions inside and outside ships is quite different, as a result also of the time elapsed since the negative effects were realized and therefore studied. The development of the normative framework in the various areas reflects these differences, but there are expectations for improvements on all fronts that need to be supported by the scientific community presenting the latest research results in this particular field of acoustics.